Method for detecting oil spots on the sea surface by means of multispectral satellite imagery (Journal of Geography and Environmental Management, 2019)
In this paper, we consider the application of object-based image analysis (OBIA) to the multispectral optical data of the average resolution of the Sentinel-2A and Sentinel-2B satellites in order to detect oil spills in the Caspian Sea.Sentinel-2 are European satellites for remote sensing of the Earth, which is part of the satellite constellation for global monitoring of the environment and security «Сореrniсus». The advantage of using these images in their availability to consumers free of charge, in their resolution and availability in real time.As an example, we analyzed two cases of oil spills in the Caspian Sea, in the area of the Oil Rocks and Kashagan fields. The purpose of this work was to determine the places and boundaries of oil pollution in the waters of the Kazakhstan sector of the Caspian Sea using multispectral optical satellite images. For this work, an OBIA analysis was used, which is a segmentation process to identify neighboring objects in images that have similar spectral characteristics and shape.It consisted of several stages, as a result of which oil pollution on the sea surface is determined.